Desain dan Pengembangan Pembelajaran E-Learning Kombinasi Google Classroom dengan Youtube sebagai Media Video Pembelajaran - Bella Salsabila; Ahmad Akhyar; Agung Setiawan; Detri Amelia Chandra (Journal on Education, 2023)
The development of increasingly innovative technology has a very good impact on the world of education. One of the innovations in the world of education is the use of e-learning. Some of the advantages of using e-learning in the learning process are fast and flexible access to learning, communication support with flexibility in language selection, content and teaching materials can be easily created and updated. There are variations of e-learning models such as Google Classroom, and several LMS (Learning Management Systems) such as YouTube. Youtube is currently the most visited and watched online video media player by internet users. With YouTube, it can facilitate the learning process, besides that, many people learn independently through YouTube. This research uses a mixed method using quantitative and qualitative methods and provides a questionnaire instrument to the respondents. The results showed that the media used was declared valid by the media validator, with an average score obtained of 4.43 or 88.6%, so the media was very valid to use. The material used was declared valid by the media validator, with an average score obtained of 4.46 or 89.2%, so the learning material was very valid to use. And the e-learning learning design that combines Google Classroom and YouTube as learning video media is declared practical with an average score of 3.52 or 88%, so the design used is very practical henceforth the learning media is declared suitable for use.